Analyzing Equilibrium in Incomplete Markets with Model Uncertainty*. (17th March 2017) - Yoshikawa, Daisuke
Abstract: In this paper, we analyze equilibrium in incomplete markets of random endowments by adopting utility indifference pricing and utility‐based pricing. Addressing model uncertainty, we also consider agents who adopt maxmin expected utility and a risk management policy. Using this framework, we demonstrate the existence of equilibrium. Moreover, we clarify the differences in the features of equilibria derived using these methods. Further, we show that the traded amount of random endowments in equilibrium by indifference pricing depends on the degree of risk aversion, initial capital, and agents' risk limits.